The Matrix (1999) - Wachowski, Andy.; Moss, Carrie-Anne.; Gloria Foster; Hugo Weaving; Joe Pantoliano; Laurence Fishburne; Marcus Chong; Keanu Reeves; Wachowski, Larry (USA Groucho II Film Partnership, 2001)
In the near future, a computer hacker named Neo (Keanu Reeves) discovers that all life on Earth may be nothing more than an elaborate facade created by a malevolent cyber-intelligence, for the purpose of placating us while our life essence is ""farmed"" to fuel the Matrix's campaign of domination in the ""real"" world. He joins like-minded Rebel warriors Morpheus (Laurence Fishburne) and Trinity (Carrie Ann Moss) in their struggle to overthrow the Matrix.
In a world of 1s and 0s...are you a zero, or The One?
Andy Wachowski
Languages : English, Turkish Subtitles : English, Turkish
Keywords: SciFi; Thriller; Action